Cost-Effectiveness of Pharmacogenomics-Guided Prescribing to Prevent Gene-Drug-Related Deaths: A Decision-Analytic Model - van der Wouden, Cathelijne H.; Marck, Heiralde; Guchelaar, Henk-Jan; Swen, Jesse J.; van den Hout, Wilbert B. (Frontiers in Pharmacology, 2022)
Aim: Prospective studies support the clinical impact of pharmacogenomics(PGx)-guided prescribing. A sub-set of these drug-gene interactions (DGIs) has been categorized as “essential” by the Dutch Pharmacogenetics Working Group (DPWG). However, the collective clinical impact and cost-effectiveness of this sub-set is yet undetermined. Here we aim to assess the clinical impact and cost-effectiveness of “essential” PGx tests to prevent gene-drug-related deaths when adopted nation-wide. Methods: We used a decision-analytic model to quantify the number and cost per gene-drug-related death prevented, from a one-year Dutch healthcare perspective. The modelled intervention is a single gene PGx-test for CYP2C19, DPYD, TPMT or UGT1A1 to guide prescribing based on the DPWG recommendations among patients in the Netherlands initiating clopidogrel, capecitabine, systemic fluorouracil, azathioprine, mercaptopurine, tioguanine or irinotecan. Results: For 148,128 patients initiating one of seven drugs in a given year, costs for PGx-testing, interpretation, and drugs would increase by €21.4 million. Of these drug initiators, 35,762 (24.1%) would require an alternative dose or drug. PGx-guided prescribing would relatively reduce gene-drug related mortality by 10.6% (range per DGI: 8.1%–14.5%) and prevent 419 (0.3% of initiators) deaths a year. Cost-effectiveness is estimated at €51,000 per prevented gene-drug-related death (range per DGI: €-752,000 – €633,000). Conclusion: Adoption of PGx-guided prescribing for “essential” DGIs potentially saves the lives of 0.3% of drug initiators, at reasonable costs.